Quantum Tunneling Mediated Interfacial Synthesis of a Benzofuran Derivative. (4th July 2019) - Paintner, Tobias; Björk, Jonas; Du, Ping; Klyatskaya, Svetlana; Paszkiewicz, Mateusz; Hellwig, Raphael; Uphoff, Martin; Öner, Murat A.; Cuniberto, Edoardo; Deimel, Peter S.; Zhang, Yi‐Qi; Palma, Carlos‐Andres; et al.
Abstract: Reaction pathways involving quantum tunneling of protons are fundamental to chemistry and biology. They are responsible for essential aspects of interstellar synthesis, the degradation and isomerization of compounds, enzymatic activity, and protein dynamics. On‐surface conditions have been demonstrated to open alternative routes for organic synthesis, often with intricate transformations not accessible in solution. Here, we investigate a hydroalkoxylation reaction of a molecular species adsorbed on a Ag(111) surface by scanning tunneling microscopy complemented by X‐ray electron spectroscopy and density functional theory. The closure of the furan ring proceeds at low temperature (down to 150 K) and without detectable side reactions. We unravel a proton‐tunneling‐mediated pathway theoretically and confirm experimentally its dominant contribution through the kinetic isotope effect with the deuterated derivative. Abstract : Tunnelblick : Die Hydroalkoxylierung einer molekularen Spezies, die auf einer Ag(111)‐Oberfläche adsorbiert ist, läuft gemäß Rastertunnelmikroskopie, ergänzt durch Röntgenphotoelektronenspektroskopie und Dichtefunktionaltheorie, noch bei Temperaturen von nur 150 K ab. Der durch Protonentunneln vermittelte Reaktionsweg wurde theoretisch aufgeklärt und experimentell anhand des kinetischen Isotopeneffekts bestätigt.